Iterative delivery of an implementation support package to increase and sustain the routine provision of antenatal care addressing alcohol consumption during pregnancy: study protocol for a stepped-wedge cluster trial - John Attia; Luke Wolfenden; Nicole Nathan; Melanie Kingsland; Olivia Wynne; Penny Reeves; Alix Hall; John Wiggers; Elizabeth J Elliott; Tameka McFadyen; Tracey W Tsang; Emma Doherty; et al. (BMJ Open)
Introduction Antenatal care addressing alcohol consumption during pregnancy is not routinely delivered in maternity services. Although a number of implementation trials have reported significant increases in such care, the majority of women still did not receive all recommended care elements, and improvements dissipated over time. This study aims to assess the effectiveness of an iteratively developed and delivered implementation support package in: (1) increasing the proportion of pregnant women who receive antenatal care addressing alcohol consumption and (2) sustaining the rate of care over time.Methods and analysis A stepped-wedge cluster trial will be conducted as a second phase of a previous trial. All public maternity services within three sectors of a local health district in Australia will receive an implementation support package that was developed based on an assessment of outcomes and learnings following the initial trial. The package will consist of evidence-based strategies to support increases in care provision (remind clinicians; facilitation; conduct educational meetings) and sustainment (develop a formal implementation blueprint; purposely re-examine the implementation; conduct ongoing training). Measurement of outcomes will occur via surveys with women who attend antenatal appointments each week. Primary outcomes will be the proportion of women who report being asked about alcohol consumption at subsequent antenatal appointments; and receiving complete care (advice and referral) relative to alcohol risk at initial and subsequent antenatal appointments. Economic and process evaluation measures will also be reported.Ethics and dissemination Ethical approval was obtained through the Hunter New England (16/11/16/4.07, 16/10/19/5.15) and University of Newcastle Human Research Ethics Committees (H-2017-0032, H-2016-0422) and the Aboriginal Health and Medical Research Council (1236/16). Trial findings will be disseminated to health service decision makers to inform the feasibility of conducting additional cycles to further improve antenatal care addressing alcohol consumption as well as at scientific conferences and in peer-reviewed journals.Trial registration number Australian and New Zealand Clinical Trials Registry (ACTRN12622000295741).